A standardized method for vertical sleeve gastrectomy bariatric surgery investigations in cancer - Ramesh, Arvind V.; Joseph, Sydney C.; Bohm, Margaret S.; Grey, Emily W.; Elasy, Joel H.; Hibl, Brianne M.; Asunloye, Oluwatosin T.; Kim, Ki-Suk; Doss, Teri D.; Pierre, Joseph F.; Cook, Katherine L.; Makowski, Liza; et al. (Frontiers in Microbiomes, 2025)
Obesity is a global epidemic that has affected the lives of over 14% of adults worldwide and over a third of Americans. Obesity is associated with the increased risk of thirteen obesity-associated cancers and poor cancer outcomes. Bariatric surgery is the most effective method of sustained weight loss and has been steadily increasing in clinical use over the past 4 decades. Importantly, bariatric surgery is established to decrease cancer risk. Vertical sleeve gastrectomy (VSG) is currently the most common bariatric surgery procedure. To evaluate underlying mechanisms of bariatric associated cancer protection, we developed a robust pre-clinical model of bariatric surgery-induced weight loss in mice. Using multiple strains, we established detailed procedures, defined best practices, and noted specific controls to include to examine mediators critical to cancer onset. This VSG protocol includes stringent pre- and post-operational measures to reduce stress-associated weight loss in obese mice to achieve rigorous and reproducible bariatric surgery-associated weight loss. In addition, we describe collection of fecal and intestinal samples as well as Peyer’s patches as important mediators of bariatric surgery’s impact on cancer risk. In conclusion, as obesity and weight loss approaches including bariatric surgery are increasingly examined in cancer risk and outcomes including immunotherapy, the establishment of robust pre-clinical interventions will allow the field to address critical underlying mechanisms mediating the benefits of weight loss and cancer.